Teri Nasi (Stolephorus sp.) Sebagai Produk Unggulan Ekspor dari Kabupaten Sumenep - Nur Farida; Selviana Ekawati; Zahra Ningsih; Imam Mudakir; Iis Nur Asyiah (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
Sumenep Regency, with its abundant marine resources, has great potential in developing superior fishery products. One of these products is terinasi. Processed anchovy (Stolephorus sp.) products have a great opportunity to penetrate the export market. This article discusses the production process, marketing and product development strategies, as well as various challenges faced by PT. Marinal Indoprima is one of the companies operating in the export and processing of fishery and marine products in Sumenep district. This research is qualitative research with data collection techniques through interviews and observation. The research subject is PT. Marinal Indoprima in Kopedi sub-district, Sumenep district. The research results show that terinasi from Sumenep has advantages and has the potential to become an export commodity in the fisheries sector. PT. Marinal Indoprima has succeeded in selling this insulated product to various countries, such as Japan, Singapore, China, Hong Kong, Thailand, the Philippines and Korea. With the right strategy, such as processing technology, strengthening local branding, and product diversification, terinasi can become a mainstay product that can encourage economic growth in Sumenep district.